Nanomechanical properties of zirconia- yttria and alumina zirconia- yttria biomedical ceramics, subjected to low temperature aging. Issue 5 (1st April 2017) - Aragón-Duarte, M.C.; Nevarez-Rascón, A.; Esparza-Ponce, H.E.; Nevarez-Rascón, M.M.; Talamantes, R.P.; Ornelas, C.; Mendez-Nonell, J.; González-Hernández, J.; Yacamán, M.J.; Hurtado-Macías, A.
Abstract: Samples of ZTA composites {80 wt%Al2 O3 +20 wt%TZ-3Y}, ATZ composites {20 wt%Al2 O3 +80 wt%TZ-3Y}, tetragonal polycrystalline zirconia (3Y-TZP), and cubic stabilized zirconia (8Y-CSZ) were prepared to study the nanomechanical properties by nanoindentation before and after low temperature aging or degradation. Moreover, structural properties and crystalline present phases were evaluated by X-Ray Diffraction (XRD) and Electron Diffraction Patterns from transmission electron microscopy (TEM). The 8Y-CSZ ceramic showed the best mechanical behavior among all the analyzed materials (ZTA, ATZ and 3Y-TZP), the 8Y-CSZ sample did not showed any phases transformations when subjected to low temperature degradation (LTD). Absolute nanohardness, Young's modulus and fracture toughness after the LTD were carried out in different samples, the obtained results, in a decreasing order were: 8Y-CSZ>ZTA>3Y-TZP>ATZ, 8Y-CSZ>3Y-TZP>ZTA>ATZ and 8Y-CSZ>3Y-TZP>ATZ>ZTA, respectively. The 8Y-CSZ ceramic, did not showed any variations in nanomechanical properties due to the absence of anisotropic behavior, manifesting high hardness, elastic modulus and relative values of fracture toughness. Perhaps this material could be candidate for biomedical applications.